The Dinaledi Intervention Program - Ncanywa, T. (Journal of Economics and Behavioral Studies, 2016)
The study seeks to examine the relationship between educational inputs, primarily the Dinaledi intervention program and schooling outcomes. The Dinaledi program is one of the government’s intervention programs to redress the inequalities and provided education resources to the previously disadvantaged communities in South Africa. The study employed a pseudo panel analysis on the attempt to answer the question of interest. Considering the random effect regression, Dinaledi schools were less likely to increase dropout rate by 0.099% with reference to non-Dinaledi schools. The pseudo panel analysis indicated a positive and significant association of the Dinaledi schools to pass rates. Further extensions of the analysis were looking at the distribution of the Dinaledi program on racial and gender issues by using the DiNardo- Fortin-Lemieux (DFL) estimation. It can be concluded that schooling outcomes can be strongly influenced by the Dinaledi intervention program with females and Blacks becoming more responsive to dropping out than their counterparts. Looking at the nature of resources and support provided to Dinaledi schools, it is recommended that the entire schooling system adopt the model to eradicate the legacy of inequality and improve schooling outcomes.